2018
DOI: 10.1016/j.ymeth.2018.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of multi-omic data and community metabolic models reveals insights into the role of hydrogen sulfide in colon cancer

Abstract: Multi-omic data and genome-scale microbial metabolic models have allowed us to examine microbial communities, community function, and interactions in ways that were not available to us historically. Now, one of our biggest challenges is determining how to integrate data and maximize data potential. Our study demonstrates one way in which to test a hypothesis by combining multi-omic data and community metabolic models. Specifically, we assess hydrogen sulfide production in colorectal cancer based on stool, muco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 80 publications
1
72
0
Order By: Relevance
“…To rule out the possibility that these contrasting results were due to differences in methods, we compared our high-throughput MTT-based assay, used in this study, with the cell counting assay, that was employed in the referred studies, on 6 cell lines, using 6 different secretomes, and found a high correlation (Pearson's r=0.813, Supplementary Figure S5). These results confirm that the observed inhibitory effects by Fusobacteriaceae strains do not depend on the applied experimental techniques, but may partly be due to use of different Fusobacteriaceae strains(Fn12230, 26 ATCC25586, ATCC23726) isolated from extra-intestinal sites (80). Specifically HCT15 cell growth was significantly inhibited by 11/16 Fusobacteriaceae strains (nine cells and three secretomes).…”
Section: Fusobacteriaceae : Enhancing or Inhibiting Growth?supporting
confidence: 77%
See 1 more Smart Citation
“…To rule out the possibility that these contrasting results were due to differences in methods, we compared our high-throughput MTT-based assay, used in this study, with the cell counting assay, that was employed in the referred studies, on 6 cell lines, using 6 different secretomes, and found a high correlation (Pearson's r=0.813, Supplementary Figure S5). These results confirm that the observed inhibitory effects by Fusobacteriaceae strains do not depend on the applied experimental techniques, but may partly be due to use of different Fusobacteriaceae strains(Fn12230, 26 ATCC25586, ATCC23726) isolated from extra-intestinal sites (80). Specifically HCT15 cell growth was significantly inhibited by 11/16 Fusobacteriaceae strains (nine cells and three secretomes).…”
Section: Fusobacteriaceae : Enhancing or Inhibiting Growth?supporting
confidence: 77%
“…In faeces of CRC patients, the genera Fusobacterium , Peptostreptococcus, Ruminococcus , and Escherichia/Shigella are enriched, while Bacteroides and Lachnospiraceae ( Roseburia, Lachnospira, Anaerostipes ) have a lower relative abundance (5,9,11,(21)(22)(23)(24)(25). Even though phyla such as Bacteroidetes are depleted, single species like enterotoxigenic Bacteroides fragilis may be enriched in some CRC patients (25)(26)(27). Comparing tumor tissue with adjacent normal tissue on the intestinal mucosa of CRC patients revealed that Fusobacterium, Prevotella, Streptococcus , and Peptostreptococcus were enriched in tumors while Blautia, Escherichia, Pseudomonas , and Faecalibacterium were enriched in the normal mucosa (5,7,9,11,(22)(23)(24)28).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has examined the role of other differentiating factors in the CRC microbiome including location [ 31 ], MSS/MSI status [ 12 ], and consensus molecular subtypes [ 32 ]. However few CRC microbiome studies account for MMR status [ 32 34 ] or microbial dynamics [ 35 ], and no studies, to our knowledge, have assessed both MMR status and microbial community dynamics. In addition, our study examines demographic, genetic, and tumor features together in a relatively large prospectively collected cohort.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a higher consumption of red and processed meats, which are high in sulfur-containing amino acids and inorganic sulfur, has been shown to increase abundances of sulfidogenic bacteria such as Bilophila wadsworthia and Pyramidobacter spp. ; these microbes are known to produce genotoxic hydrogen sulfide in the gut, thereby inducing DNA damage in intestinal epithelial cells and promoting carcinogenesis (10)(11)(12)(13). In another example, intake of dietary fibers results in enrichment of Bifidobacterium and Lactobacillus spp., which are capable of fermenting dietary fibers into short-chain fatty acids (SCFAs) (14).…”
mentioning
confidence: 99%